Fiscal policy, institutions and governance in selected South Asian countries - Tariq Hussain; Muhammad Wasif Siddiqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The objective of the study is to analyze the cyclicality of Fiscal Policy among Institutions (Economic and Political) and governance indicators from 1980-2010 in major South Asian Countries. Fiscal policy is a major source in the hands of the government to achieve higher level of economic growth. This policy can perform efficiently in the presence of strong institutions with good governance. The main purpose of fiscal policy is to bring stability in the economy. Therefore, developed countries adopt counter cyclical policies but developing countries adopt pro cyclical fiscal policy. Developing countries adopt pro cyclical fiscal policy due to weak institution and poor governance. Pooled OLS, Fixed effects and 2SLS approaches are used to evaluate whether the fiscal policy is counter cyclical or pro cyclical. It is found that fiscal policy is pro cyclical, economic and political institutions don't perform effectively and governance is poor. In order to bring stability in economic growth in South Asian countries, counter cyclical growth policies should be adopted.
Keywords: 330; cyclicality; fiscal policy; institution; governance; South Asia